A historical loss approach to community bank stress testing - Fang, Cao; Yeager, Timothy J. (Journal of Banking & Finance, 2020)
We develop a top-down macro stress test that assesses a community bank's ability to withstand a severe and prolonged period of high credit losses. The model groups banks by geography and subjects them to the 90th percentile chargeoff rates that banks experienced between 2008 and 2012. Because of local data limitations, our historical loss approach better reflects patterns of community bank stress than a linear econometric approach that estimates the relationship between macroeconomic conditions and bank performance. We put all U.S. community banks at year-end 2017 through the test and highlight two results. First, banks are much better prepared to withstand an adverse shock than they were on the verge of the financial crisis because banks have shifted away from the riskiest loan types. Second, the Tax Cuts and Jobs Act of 2017 has increased bank insolvency risk from an adverse shock in 2018 because the higher bank capital is more than offset by the weaker automatic stabilizer effect from operating losses.